Report of the virtual RTB ISC Annual Meeting 2021. The Grand Finale. July 7-9, 2021 - Bentley, J.W.; Thiele, Graham; Bonaiuti, Enrico (International Potato Center, 2021)
OBJECTIVES • Progress by flagships shared with Independent Steering Committee (ISC) and RTB community • Reflection of RTB achievements and challenges • Contribute to the transition to One CGIAR with collective knowledge assets • Consolidate lessons learnt for implementation of new initiatives